2022
DOI: 10.3390/met12010157
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behaviour and Failure Mode of High Interstitially Alloyed Austenite under Combined Compression and Cyclic Torsion

Abstract: multiaxial stress states frequently occur in technical components and, due to the multitude of possible load situations and variations in behaviour of different materials, are to date not fully predictable. This is particularly the case when loads lie in the plastic range, when strain accumulation, hardening and softening play a decisive role for the material reaction. This study therefore aims at adding to the understanding of material behaviour under complex load conditions. Fatigue tests conducted under cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This compressive creep occurs as soon as a critical angle for the cyclic torsion is exceeded, such that it remains unclear whether an equivalent stress of the applied stress tensor can be defined that describes this deformation mode with sufficient accuracy. Ngeru et al [ 11 ] reported similar behavior in a high nitrogen stainless steel subjected to similar loading conditions. It is noted here, that this kind of creep deformation is purely mediated by dislocation motion, whereas diffusive or other thermally activated mechanisms do not play a role.…”
Section: Introductionmentioning
confidence: 74%
“…This compressive creep occurs as soon as a critical angle for the cyclic torsion is exceeded, such that it remains unclear whether an equivalent stress of the applied stress tensor can be defined that describes this deformation mode with sufficient accuracy. Ngeru et al [ 11 ] reported similar behavior in a high nitrogen stainless steel subjected to similar loading conditions. It is noted here, that this kind of creep deformation is purely mediated by dislocation motion, whereas diffusive or other thermally activated mechanisms do not play a role.…”
Section: Introductionmentioning
confidence: 74%
“…Some researchers have investigated and discussed the growth behavior of torsional fatigue cracks under axial tension or compression superposition (Zhang and Akid, 1997a;Makabe and Socie, 2001;Yang and Kuang, 2005;Macek, 2021;Ngeru et al, 2022). Zhang and Akid (1997b) found that in pure cyclic torsion, cracks on the surface of high strength spring steel and 316L stainless steel both extended longitudinally in mode II.…”
Section: Introductionmentioning
confidence: 99%
“…An axial tensile mean stress promoted a change in the direction of the mode II crack from the longitudinal direction to a plane normal to the specimen axis in the high strength steel but not in the stainless steel. Nevertheless, Ngeru (2022) believed that the static compressive stress facilitated the Stage I (mode II) crack to change direction from the axial direction to a plane perpendicular to the specimen's axis. Yang and Kuang (2005) studied the crack growth of carbon steel S45 under cyclic torsion with axial static tension/compression, using specimens with a straight-fronted surface flaw in the cross section.…”
Section: Introductionmentioning
confidence: 99%